NILAI KESUKAAN KONSUMEN TERHADAP TEH DAUN GAHARU (Aquilaria malaccensis Lamk) BERDASARKAN LETAK DAUN PADA BATANG - Nora Adriana; Ridwanti Batubara; Elisa Julianti (Program studi Kehutanan USU, 2015)
Agarwood is a product of non-timber forest product are high value and are exported to foreign countries. Utilization of wood still focused on the use of agarwood tress, sap and skin is more often used as a distinctive aroma produced. Therefore, it is necessary to study on the effect of the aloe plant leaf leaves of that aloes. The purpose of this study is to determine the level of preference for the public to tea agarwood (A. malaccensis Lamk) based on the location of the leaves on the stem. The result showed that the level of public preference for tea agarwood (A. malaccensis Lamk) are on a scale of 3-4 is enough like to like. Consumers prefer tea from the leaves of the aloes are in the middle position on the aloe tree. Keyword : agarwood leaves, agarwood tea leaves, the level preference.